Useful Genioplasty for Repeated Recurrent Sleep Apnea of Congenital Anomalies and Its Evaluation - Hiromi Kino, MD; Koichi Ueda, MD, PhD; Yuka Hirota, MD, PhD; Toyoko Okamoto, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Congenital facial anomalies with hypoplasia of the midface or lower face are associated with obstructive apnea syndrome. Although such patients underwent bone advancement surgery and their sleep apnea improved in the short term, it often recurred several years after surgery. It is difficult to perform another major osteotomy because of impairment of the facial contour or prior orthodontic treatment. Genioplasty was performed for genioglossus muscle advancement in patients with congenital anomalies and repeated sleep apnea. In this study, we evaluated the usefulness of this procedure and the mechanism for the improvement of sleep apnea. Methods:. Six patients were included: three with syndromic craniosynostosis, two with Treacher-Collins syndrome, and one with micrognathia by Goldenhar syndrome. Patients who had recurrence of sleep apnea after previous maxillomandibular osteotomies, or advancement and orthodontic treatment, received genioplasty for genioglossus muscle advancement. The patients were evaluated by body mass index, simple polysomnography, hyoid bone position on cephalogram, and the airway area on computed tomography images pre- and postoperatively. Results:. Polysomnography showed a significant improvement in the apnea-hypopnea index. Cephalometric measurement showed significant results of the hyoid bone position from point B and the ramus plane. However, no significant results were obtained in the airway area assessment. Conclusions:. Genioplasty for genioglossus muscle advancement can improve apnea-hypopnea index by moving the hyoid bone forward. Genioplasty was useful in patients with congenital anomalies who had a recurrence of sleep apnea after several procedures.